IMPLEMENTATION OF A REHABILITATION NURSING PROGRAM IN ELDERLY PEOPLE WITH FRAGILITY/DISUSE SYNDROME - CASE STUDY - Ana Gil; Filipa Sousa; Maria Manuela Martins (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: The person with disuse syndrome may present balance changes and a condition of fragility, with a consequent deficit in the performance of their activities of daily living. Objective: To identify the gains that are sensitive to rehabilitation nursing care with a program of therapeutic activities and exercises to restore balance and improve frailty. Method: Qualitative study, case study. The case of an elderly person with disuse syndrome admitted to an adult hospital is presented. The ethical principles in research have been followed. Results: Gains in postural balance and fragility were evidenced after the implementation of 9 sessions of therapeutic exercises and balance training. Conclusion: The implementation of rehabilitation nursing care proved to be effective in recovering body balance in people with disuse syndrome, as well as in improving frailty, optimizing their autonomy.